Design And Development Documentary Video of Belakang Padang Sub-district - Delphy Lijaputra; Tony Wibowo (Universitas Internasional Batam, 2024)
With the increasing development of the technological era, Technology has become one of the aspects of interdependence in humans’ lives or activities, even in Economics, Politics, Education, and even the Arts. These happen because of the efficiency, fastness, and comprehensiveness of sharing information. Sharing information digitally has become one of the most frequently used methods, especially in the application of rebranding. One of the rebranding methods is through multimedia content, such as videography, photography, and illustrations. One of the problems faced by the Belakang Padang sub-district is a lack of branding in introducing Belakang Padang itself. Therefore, a documentary video was developed that helped the Belakang Padang sub-district. Designing and developing a documentary video aims to increase the opportunities to attract tourism by providing an overview or introduction to the Belakang Padang sub-district. The result of the Documentary video was uploaded to the YouTube platform with a duration of 7 minutes and 25 seconds.